The effect of low level laser therapy on pain during dental tooth-cavity preparation in children - (:unkn) unknown (Springer Verlag, 2011)
Aim: To evaluate the effect of low level laser therapy on pain during cavity preparation with laser in paediatric dental patients. Study Design and Methods: The study was carried out on 10 children aged 6 to 9 years old for a total of 20 primary molar teeth. For laser preparation an Er: YAG laser was used. Half of the preparations were treated by low level laser therapy (LLLT) before laser preparation and the remaining half without LLLT (non-LLLT) before laser preparation. All cavities were prepared by ER:YAG laser, restored with light-cured composite resin following the application of acid etching and bonding agent. Children were instructed to rate their pain on the visual analogue scale (VAS) from 0 to 5 points. Statistical analyses were performed using Mann Whitney U test. Results: VAS Median (min-max) scores were 1(0-2) for LLLT and 3(1-4) for the non-LLT treated children. Between LLLT and non-LLLT groups results were statistically significant (p<0.01). Conclusions: The use of LLLT before cavity preparation with laser decreased pain in paediatric dental patients.
Keywords: Children; Low level laser therapy; Pain